Blending traditional sales techniques with livestream commerce: strategies for personal selling and streamer engagement - Hsunchi Chu (Cogent Business & Management, 2024)
The advent of livestream technology signifies a significant paradigm shift in consumer engagement and sales strategies within the digital era. This study explores the transformation from traditional salespeople, known for their direct selling techniques, to modern-day livestreamers who leverage technology to engage with a global audience. Through participant observation and in-depth interviews, our research identified five pivotal themes that underscore the innovative practices and roles of livestream commerce (LSC) streamers: Evolving Expertise, Building Digital Rapport, Interactive Engagement, Exclusive Online Offers, and Content-Centric Connection. These themes demonstrate how livestreamers adeptly integrate and adapt traditional sales principles—such as Adaptive Selling, Need Satisfaction, and Relationship Orientation—into their digital interactions, catering to evolving consumer needs and providing unique engagement and value creation opportunities. Our findings highlight significant shifts in sales roles, emphasizing the crucial integration of digital technology and the transformation of customer relationships into deeper digital connections. This study showcases the essential role of digital charisma in shaping the future of retail, setting new standards for conducting sales interactions in the digital age.
Keywords: 650; Livestream commerce; streamer; personal selling; adaptive selling; customer relationship management; social commerce